First experiences in a school-based practicum: Pre-service teachers’ emotion and perceived benefits towards the program - Ika Wahyuni Lestari (Universitas Merdeka Malang, 2020)
School-based practicum is an inseparable part of Indonesian teacher education. The aim of the present study is to explore initial experiences of pre-service English teachers (PSETs) on a school-based practicum program. Under a qualitative case study, four first-year PSETs of a private university in Yogyakarta, Indonesia were purposefully selected as the participants. Data were collected through semi-structured interview, the handbook of the program, and the PSETs’ reflective journals. The results suggested that the PSETs underwent positive emotion during the practicum. Factors contributing to the emotion and benefits the PSETs perceived were also reported. At last, implications on future implementation of school-based practicum were addressed. DOI: 10.26905/enjourme.v4i2.4228